REPRESENTASI KRITIK SOSIAL DALAM FOTO CERITA AMP.ANTARAFOTO.COM "ANCAMAN LIMBAH DARI BISNIS BUSANA" (Analisis Semiotika Roland Barthes) - Haniyah Rizki Oktaviani (2021)
Photo, especially photojournalism, is one of the tools in the delivery of social criticism. One of them is depicted in a photo of the story "The Threat of Waste from the Fashion Business" by Muhammad Adimaja on the site antarafoto.com. The photo of the story, tells about how the fashion industry, especially fast fashion, is causing threats or adverse impacts, especially on the environment. If look at the problems posed by this industry, then it is not only an industrial problem, but also a social problem that reaps criticism. Through this study, the Author aim to find out the representation of social criticism in the photo story "The Threat of Waste from Fashion Business". In this study, the Author used qualitative research methods, with Roland Bharthes's semiotic analysis method. The Author uses the reading of six connotation procedures of photographic messages explained by Roland Barthes, that is Trick Effect, Pose, Object, Photogenia, Aestheticism, and Syntax. The results show that in the photo story "The Threat of Waste from the Fashion Business", represents a social criticism aimed at the capitalist climate and consumerism culture in the fast fashion industry. Keywords: Representation, Social Criticism, Fast Fashion Industry, Photo Story, Semiotic of Roland Barthes